2020
DOI: 10.3892/etm.2020.8719
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role of miR‑338‑3p in peripheral blood and placenta of patients with pregnancy‑induced hypertension

Abstract: The present study aimed to investigate the role of miR-338-3p in pregnancy-induced hypertension (PIH), and its effects on human trophoblast cells in vitro. Quantitative real-time PCR was used to detect miR-338-3p expression. Human trophoblast HTR8/SVneo cells were transfected with miR-338-3p mimics. Effects of miR-338-3p on cell proliferation, invasion and metastasis, and anoikis resistance were detected by CCK-8 assay, Transwell chamber assay, flow cytometry and western blot analysis, respectively. Bioinforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…p38 is a downstream protein kinase of the Ca 2+ signal, and once activated, it initiates the apoptosis‐related transcription factors, which in turn regulate apoptosis (Dziegielewska et al, 2014; Liu et al, 2012). The activated p38 can phosphorylate AKT that is a serine/threonine kinase consisting of a sequence of more than 480 amino acids (Li et al, 2020; Tikoo et al, 2009). However, it has been well documented that p38 activation can reduce the expression of the survival protein AKT, thereby promoting pro‐apoptotic signaling (Ketteler et al, 2020; Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…p38 is a downstream protein kinase of the Ca 2+ signal, and once activated, it initiates the apoptosis‐related transcription factors, which in turn regulate apoptosis (Dziegielewska et al, 2014; Liu et al, 2012). The activated p38 can phosphorylate AKT that is a serine/threonine kinase consisting of a sequence of more than 480 amino acids (Li et al, 2020; Tikoo et al, 2009). However, it has been well documented that p38 activation can reduce the expression of the survival protein AKT, thereby promoting pro‐apoptotic signaling (Ketteler et al, 2020; Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…HIF1α, a key regulator of intracellular oxygen metabolism, plays an important role in the development of the tumor ( 35 ). HIF1α is significantly upregulated to maintain trophoblasts in a proliferative, non-invasive and immature phenotype, which share some similarities with tumor cells in the biological processes, during the initial phase of embryonic development ( 23 , 36 ). After that, oxygen levels in the intervillous spaces increase from 2% O 2 before 9 weeks to 8% O 2 at 10 to 12 weeks of pregnancy ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…TargetScan online database was used to predict the target gene of miR-320b, and literature review showed that AKT3 was closely related to the occurrence and development of hypertension (Li et al 2020). The conservative site sequences of miR-320b target gene AKT3 with the lowest free energy were selected, and the wild-type and mutant AKT3 seed regions were synthesized in vitro by chemical synthesis.…”
Section: Luciferase Reporter Gene Assaymentioning
confidence: 99%